How Should Legislation Be Made During the Digital Age? Indonesian Outlook - Al-Fatih, Sholahuddin (KnE Social Sciences, 2024)
This article tries to explain how legislation should be made in the digital era. Because digitalization is something that cannot be rejected or avoided. Therefore, the dynamics of the digital era must also be responded to by law, especially in the study of legislation. Using normative research methods, this article found several important things, including 1) Indonesia does not yet have many legislative products regarding the digital era, there are only a few, for example, the IET Law, the Personal Data Protection Law, and the like. 2) Indonesia needs to respond to developments in the digital era by issuing special regulations, for example, the Metaverse Bill, the Digital Money Bill, AI Bill, and the like. 3) The method for establishing legislation in the digital era must also adapt to the times. So, it does not rule out the possibility that in the digital era, there is a known method for establishing statutory regulations other than the existing conventional methods, such as RIA or omnibus law. Keywords: legislation, digital age, Indonesia